(untitled) (Gestão & Regionalidade, 2009)
Contemporary western organizations appear to be caught in neophily, i.e., a cult of newness and novelty. As traditional means of organizational transformation - and profit maximization in particular - have broadly proven insufficient or to have completely failed, contemporary capitalism has turned the Old into an antiquated object of hatred. As the Old, and thus the past, is split off, the New - because it is new - is guaranteed to be better. Organizational structures and processes that previously served as more or less reliable containers for both labour and capital are now regarded as old wineskins that have served their purpose and belong on the ’scrapheap of history’. This paper emanates from the working hypothesis that betrayal and cynicism, in the context of organizational transformation, cannot sufficiently be understood from a perspective limited to individual psychopathology but has to take the organization as a whole into account. Keywords: Betrayal, Cynicism, Organizational Transformation, Socio-analysis.